Combination of Autogenic Relaxation and Lavender on the Anxiety of Primigravida Pregnant Women Third Trimester - Sembiring, Desi Br (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
Anxiety about childbirth is a problem that is always experienced by every pregnant woman. Anxiety for pregnant women is caused by a lack of preparation for childbirth. Anxiety if not treated can cause adverse effects on the mother and fetus. The aim was to determine the effect of a combination of autogenic relaxation and lavender aromatherapy on the anxiety of third trimester pregnant women. This research uses quantitative methods and the sampling technique is accidental sampling. The instrument used in this study was to use a questionnaire using the PRAQ-R2 scale (Pregnancy Related Anxiety Questionnaire-Revised). The population and sample in this study were third trimester pregnant women with a total sample of 34 respondents. This research was conducted from January to May 2023. Bivariate data analysis used paired t-test analysis. The results of the analysis obtained a p value of 0.000 (<0.05), it can be concluded that there is an effect of a combination of autogenic relaxation and lavender aromatherapy on the anxiety of third trimester pregnant women.